2015
DOI: 10.1590/0034-737x201562040012
|View full text |Cite
|
Sign up to set email alerts
|

A aplicação foliar de molibdênio na fase de enchimento de vagens do feijão-comum pode reduzir a qualidade da semente

Abstract: A aplicação foliar de molibdênio na fase de enchimento de vagens do feijão-comum pode reduzir a qualidade da sementeCom o objetivo de aprimorar a tecnologia de produção de sementes ricas em molibdênio (Mo), foram avaliados os efeitos da aplicação foliar de 600 g ha -1 de Mo na qualidade fisiológica da semente de feijão. Em campo, essa dose de Mo foi aplicada na fase V4 (terceira folha trifoliolada), ou parcelada de duas a quatro vezes e aplicada em V4, R6 (floração), R7 e, ou, R8 (enchimento de vagens). A apli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…at the R8 stage may reduce seed quality (Vieira et al, 2015). In future studies, doses lower than 200 g Mo ha -1 applied at the R8 stage should be included as a treatment when trying to improve Mo accumulation in seed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…at the R8 stage may reduce seed quality (Vieira et al, 2015). In future studies, doses lower than 200 g Mo ha -1 applied at the R8 stage should be included as a treatment when trying to improve Mo accumulation in seed.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of Mo application during the reproductive stage of the common bean has not been confirmed in controlled studies. In a study conducted in the Zona da Mata region, 200 to 300 g Mo ha -1 sprayed at the R8 stage (pod filling) of the common bean reduced seed quality as evaluated by germination and accelerated aging tests (Vieira et al, 2015). Thus, Mo application at the common bean's reproductive stage should concentrate on R5 (pre-flowering), R6 (flowering) and R7 (pod formation) stages in trying to improve SMoC.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Vieira et al (2016), Mo was applied at V4, R5 (bud initiation), and R7 (pod formation) growth stages. According to Vieira et al (2015), application of Mo at the seed filling (R8) growth stage should be avoided due to the risk of reducing seed physiological quality (germination and vigor). Vieira et al (2016) found that seed vigor was greater with 100 g ha −1 than with 600 g ha −1 of Mo in one trial.…”
Section: Core Ideasmentioning
confidence: 99%
“…Therefore, although with a final stand density 19% lower than that obtained with low-Mo seeds (Figure 1d), plants raised from high-Mo seeds yielded 42% more than those originated from low-Mo seeds (Figure 1e). The lower stand density for plants raised from high-Mo seeds may be due to the 400 g ha −1 of Mo applied at the pod-filling stage of the plants from which high-Mo seeds were harvested, as long as, according to Vieira et al (2015), over 200 g ha −1 of Mo applied at common bean pod-filling may have decreased the quality of the seeds. Thus, the effects of rates and split application of Mo in different cowpea reproductive growth stages on both seed Mo content and seed quality should be evaluated in further studies to improve the technology of pro-ducing Mo-enriched seeds.…”
Section: Effects Of Seed Mo Content and Bradyrhizobial Inoculation On Cowpea Yieldmentioning
confidence: 99%